AGRICULTURE FINANCING AND ECONOMIC GROWTH IN NIGERIA - Obansa, S. A. J.; Maduekwe, I. M. (European Scientific Journal, ESJ, 2013)
The importance of agricultural surplus for the structural transformation accompanying economic growth is often stressed by development economists. This lead to the question: Does agriculture financing matters in the growth process? To this end, the need to investigate the impact of agriculture financing on economic growth appears more imperative for Nigeria. This paper employed secondary data and some econometric techniques such as Ordinary Least Square (OLS); Augmented Dickey-Fuller (ADF) unit root test; Granger Causality test. The results of the various models used suggest that there is bidirectional causality between economic growth and agriculture financing; and there is bidirectional causality between economic growth and agricultural growth. It further suggests that productivity of investment will be more appropriately financed with foreign direct private loan, share capital, foreign direct investment and development stocks. And also capital-output ratio will be more appropriate financed with multilateral loan, domestic savings, Treasury bill, official development assistant, foreign direct investment and development stock. It is recommended that maintenance of credible macroeconomic policies that is pro-investment; and debt-equity swap option are necessary for a agricultural-led economic growth.